Interactive web-based tool for evaluating the spread of bovine tuberculosis and brucellosis in Colombia - Nelson E. Arenas (Universidad de Antioquia, 2020)
Background: Bovine tuberculosis (BTB) and brucellosis are associated with devastating losses in the livestock sector in Colombia and even in developed countries. Real-time disease surveillance is a key strategy to control and eradicate infectious disease outbreaks. Objective: To design an epidemiological tool for monitoring BTB and brucellosis in Colombia. Methods: An interactive platform for disease mapping of BTB and brucellosis during an observation period between years 2004 and 2019 was designed. Results: Our analysis showed that the provinces of Cundinamarca and Valle del Cauca are regions affected by BTB and brucellosis epidemics, respectively (p<0.001). Furthermore, increased case detection of BTB was reported in 2012 and brucellosis in 2019 (p<0.001). Conclusions: This epidemiological platform allows tracking BTB and tuberculosis hotspots, identifying trends over time, and provides useful information to animal health authorities for designing new strategies in control programs.